Preparing for implementation of family-integrated neonatal care by healthcare providers in a district hospital of Limpopo Province - Morogwana Anna Shokane; Ramadimetja Shirley Mogale; Carin Maree (Elsevier, 2023)
Background: Parents of babies admitted to the neonatal unit experience considerable stress related to the neonatal environment and condition of the neonate. During admission, care is provided by healthcare providers and parents only visit their neonates during scheduled times. In family-integrated neonatal care parents are primary caregivers in neonatal health. Aim: The aim of the study was to develop and implement strategies of family integrated neonatal care in a district hospital of Limpopo. Design: Action research, Piggot Irvine Problem Resolving Action Research model was utilized in the study. Methods: A quantitative tool was utilized to collect data on the well-being of the neonates. Two focus groups were held to explore the experiences of health care providers on provision of neonatal care in Limpopo Province. Data analysis: Descriptive statistics was used to analyse quantitative data and the Tesch eight steps of data analysis was used to analyse qualitative data. Results: Six sub themes emerged during the focus groups, namely,1) HIV-positive mothers' unwillingness to breastfeed; 2) failure of the HIV-positive mothers to disclose their status to partners 3) failure of the mother to sustain kangaroo mother care after discharge; 4) incorrect Apgar scoring by midwives and medications by doctors in the labour ward; 5) shortage of resources in the neonatal unit; and 6) roles of family members in the neonatal unit. On assessment of the neonates' well-being, it was found that most lost weight, while some neonates had a prolonged stay in the neonatal unit.Strategies of implementation of family integrated neonatal Care were developed by a steering committee. Conclusion: The conducted situational analysis highlighted the need for implementation of family integrated neonatal care, in which parents would become primary caregivers for their own neonates. Further research is required to explore the experiences of mothers during the implementation of family integrated neonatal care.